DEVELOPING SPEECH AND THINKING IN ELEMENTARY SCHOOL STUDENTS DURING NATIVE LANGUAGE LESSONS - Zeripboyeva Kumushoy Jamoladdin qizi; Ibragimova Lizaxan Avezovna (Web of Journals Publishing, 2024)
This article discusses exercises designed to enhance students' knowledge and skills in native language classes in elementary grades, utilizing methodological techniques to develop their speech processes.
Keywords: native language, pedagogue, methodological guides, principle of scientific and comprehensibility, speech, thinking.